2019
DOI: 10.1039/c9ra05923g
|View full text |Cite
|
Sign up to set email alerts
|

TiBALDH as a precursor for biomimetic TiO2 synthesis: stability aspects in aqueous media

Abstract: Factors affecting TiO2 biomineralization using TiBALDH as precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…However, it was recently shown to be a cyclic and tetranuclear oxo-lactate complex of Ti­(IV) (Figure A) that exists in equilibrium with tris­(lactato-titanate) complexes (Figure B) and anatase nanoparticles stabilized by surface-capping lactate ligands according to the reaction ,, The co-existence of multiple species in commercial TiBALDH preparations means that solution conditions have a profound influence on synthetic outcomes. Indeed, Kessler and co-workers showed that addition of polar solvents to solutions of TiBALDH shifts the equilibrium of reaction to the right and promotes the formation of ∼3 nm anatase nanoparticles, while Hernández-Gordillo et al found that acidification in citrate and acetate buffers shifts the equilibrium to the left and causes an increase in the amount of soluble Ti­(IV) …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was recently shown to be a cyclic and tetranuclear oxo-lactate complex of Ti­(IV) (Figure A) that exists in equilibrium with tris­(lactato-titanate) complexes (Figure B) and anatase nanoparticles stabilized by surface-capping lactate ligands according to the reaction ,, The co-existence of multiple species in commercial TiBALDH preparations means that solution conditions have a profound influence on synthetic outcomes. Indeed, Kessler and co-workers showed that addition of polar solvents to solutions of TiBALDH shifts the equilibrium of reaction to the right and promotes the formation of ∼3 nm anatase nanoparticles, while Hernández-Gordillo et al found that acidification in citrate and acetate buffers shifts the equilibrium to the left and causes an increase in the amount of soluble Ti­(IV) …”
Section: Results and Discussionmentioning
confidence: 99%
“…Indeed, Kessler and coworkers showed that addition of polar solvents to solutions of TiBALDH shifts the equilibrium of reaction 1 to the right and promotes the formation of ∼3 nm anatase nanoparticles, 35 while Hernańdez-Gordillo et al found that acidification in citrate and acetate buffers shifts the equilibrium to the left and causes an increase in the amount of soluble Ti(IV). 46 We propose that a low pH and the presence of citrate ions destabilize liganded lactates and increase the ability of the highly basic sfGFP-Car9 to act as a ligand for oxo clusters and partially dissolved anatase nanoparticles. With more Ti(IV) available, growth proceeds through facilitated hydrolysispolycondensation reactions in a process that could be further enhanced by charge compensation between the negatively charged surface of titania clusters and positively charged regions on the surface of sfGFP (Figure 6A).…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
See 1 more Smart Citation
“…TiBALDH solutions contain several species that are in equilibrium among themselves and with TiO 2 , including mononuclear species. At neutral or slightly basic pH, mononuclear hydrated titanium species also include Ti(OH) 4 [ 5 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectra provide, in fact, detectable shifts but they cannot assess the binding beyond any reasonable doubt and, on the other side, the addition of TiBALDH to the crystals does not disrupt them, allowing for good resolution data collection. In this manuscript, we thus provide the first structure-based experimental evidence that among the possible mononuclear titanium species considered in the literature [ 62 ], Ti(OH) 4 does interact with lysozyme before precipitation starts and that the interaction is electrostatic in nature. The interaction appears, in line with expectation, to be directed in an area where several arginine residues are present but, unexpectedly, appears to be mediated by an intervening water molecule; in fact, during its diffusion into the crystal, the titanium(IV) species happens to be trapped in a solvent channel created by symmetry mate molecules, because of steric hindrance and charge accumulation in the channel.…”
Section: Discussionmentioning
confidence: 99%